Spider woman stories : legends of the Hopi Indians - Mullett, G.M. (Tucson & London : The University of Arizona Press, 1979)
Presents Hopi Indian legends of the creation, the adventures of the hero Tiyo, and the Twin War Gods and their activities on behalf of the Hopi
Keywords: Hopi Indians -- Legends; Indians of North America -- Arizona -- Legends